I am AmeriBritSouthAfrican‐Zambian: Multidimensional remote acculturation and well‐being among urban Zambian adolescents. (7th August 2015) - Ferguson, Yuna L.; Ferguson, Kim T.; Ferguson, Gail M.
Abstract : One impact of globalisation is that adolescents today are frequently exposed to the values, attitudes and norms of other nations without leaving their own backyards. This may lead to remote acculturation—cultural and psychological changes experienced by non‐migrant individuals having indirect and/or intermittent contact with a geographically separate culture. Using quantitative and qualitative data, we examined multidimensional remote acculturation among 83 urban Zambian adolescents who are routinely exposed to U.S., U.K. and South African cultures through traditional and social media and materials/goods. Cluster analyses showed 2 distinct groups of adolescents. "Traditional Zambians, TZs" (55.4%) were significantly more oriented towards Zambian culture and reported a higher level of obligation to their families and greater interdependent self‐construal compared with "Westernised Multicultural Zambians, WMZs" (44.6%), who were more oriented towards U.S., U.K. and South African cultures. Furthermore, remote acculturation predicted somewhat lower life satisfaction among WMZs. These results demonstrate that individuals' behaviours, values and identity may be influenced by multiple geographically distant cultures simultaneously and may be associated with psychological costs.